Evidence-based practices - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Bingley, U.K. : Emerald, 2013)
This volume focuses on evidence-based practices (EBPs) , supported, sound research studies documenting their effectiveness with a target population. As such, EBPs have significant potential to improve the outcomes of learners with learning and behavioral disorders. However, a number of obstacles exist in identifying, conceptualizing, adopting, and maintaining EBPs that have prevented educators from realizing their potential benefits. The chapters in this volume address many of these issues, with the goal of improving stakeholders? ability to identify and implement EBPs. Chapters discuss the following topics: appraising systematic evidence-based reviews, using single-subject research to identify EBPs, legal issues, implementation fidelity and EBPs, guidelines for implementing EBPs, obstacles to implementing EBPs, teacher preparation and EBPs, EBPs for learners with learning disabilities, EBPs for learners with behavioral disabilities, EBPs for learners with autism spectrum disorders, EBPs in early childhood special education, EBPs in special education in Australia.
ch. 1. Evidence-based practices in learning and behavioral disabilities : the search for effective instruction / Bryan G. Cook, Melody Tankersley, Timothy J. Landrum -- ch. 2. Evidence-based education and best available evidence : decision-making under conditions of uncertainty / Ronnie Detrich, Timothy A. Slocum, Trina D. Spencer -- ch. 3. Appraising systematic reviews : from navigating synopses of reviews to conducting ones own appraisal / Ralf W. Schlosser, Parimala Raghavendra, Jeff Sigafoos -- ch. 4. Adapting research-based practices with fidelity : flexibility by design / LeAnne D. Johnson, Kristen L. McMaster -- ch. 5. Synthesizing single-case research to identify evidence-based treatments / Kimberly J. Vannest, Heather S. Davis -- ch. 6. Utilizing evidence-based practice in teacher preparation / Larry Maheady, Cynthia Smith, Michael Jabot -- ch. 7. The peer-reviewed requirement of the IDEA : an examination of law and policy / Mitchell L. Yell, Michael Rozalski -- ch. 8. From research to practice in early childhood intervention : a translational framework and approach / Carol M. Trivette, Carl J. Dunst -- ch. 9. Effective educational practices for children and youth with autism spectrum disorders : issues, recommendations, and trends / Richard Simpson, Stephen Crutchfield -- ch. 10. Constructing effective instructional toolkits : a selective review of evidence-based practices for students with learning disabilities / Tanya E. Santangelo ... [et al.] -- ch. 11. Evidence-based practice in emotional and behavioral disorders / Timothy J. Landrum, Melody Tankersley -- ch. 12. Evidence-based practices in Australia / Jennifer Stephenson, Mark Carter, Sue ONeill.
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Teaching Methods & Materials -- General; Education -- Experimental Methods; Teaching of specific groups & persons with special educational needs; Curriculum planning & development; Children with disabilities -- Education